ST Logistics: Distributing Consumer Goods in China - CHEN, Frank Y. (Institutional Knowledge at Singapore Management University, 2001)
This paper describes the experience gained from a research collaboration between a group of researchers at the National University of Singapore and logistics executives in Sembcorp Logistics (formerly ST Logistics), in the latter's effort to develop a marketing and strategic planning software tool to enhance its third party logistics (3PL) services in China. As China opened up its economy in the late 1980s, many Western consumer goods manufacturers set up plants or formed joint ventures in China in an attempt to capture this huge market. While the production process can be easily built on the existing technologies and can be efficient costwise, the distribution process is still a challenge because of the backward nature of the infrastructure and the bureaucratic roadblocks, resulting in very high supply chain transaction costs. Consequently, most manufacturers turn to third-party logistics providers (3PLs) who have the required logistics expertise to operate in China. One of the leading 3PLs in China is Shenzhen ST-Anda Logistics (ST-Anda), a joint venture between Sembcorp Logistics and China Merchant Holdings. It has an existing pan-China network of distribution centers. Recently, to improve services to their customers, ST-Anda started planning for the expansion of their logistics distribution network. An OR/MS modeling approach was taken to help them in this venture.